LEVANTAMENTO URBANÍSTICO DA ORLA FLUVIAL DO PORTO DE CORUMBÁ, MS, BRASIL (Terr@ Plural, 2019)
The analysis of environmental perception generates efficient diagnoses in the definition of guidelines for urban interventions in the field of urban and regional planning. In urban planning, surveys and analyzes are necessary considering, in an integrated manner, the physical, environmental, legal and social characteristics of the landscape to be requalified. This article presents an analysis and interpretation of the landscape of the general port of Corumbá from the beginning of Prainha Vermelha to the Cacimba da Saúde area with the purpose of assisting in the elaboration of guidelines for the planning of degraded, misused and abandoned spaces, enabling the development of projects of urban requalification and landscaping consistent with the needs and potential of the region. Data pointed to serious urban problems as irregular use of the waterfront, poor sanitary sewage, among others. Guidelines for the requalification of spaces and intervention projects are presented.